2018
DOI: 10.1380/ejssnt.2018.247
|View full text |Cite
|
Sign up to set email alerts
|

4D-Data Acquisition in Scanning Confocal Electron Microscopy for Depth-Sectioned Imaging

Abstract: We propose an experimental depth-sectioned imaging method based on annular dark-field scanning confocal electron microscopy (ADF-SCEM). Four-dimensional (4D) datasets, consisting of 2D probe images taken at every probe position during 2D raster scanning, were acquired with an aberration-corrected scanning transmission electron microscope. A series of depth-sectioned images were constructed by processing a single 4D dataset. A pinhole and a stage-scan system used in earlier studies were not required in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…As a special type of segmented detectors, pixelated detectors provide an ultimate detector form for STEM imaging that incorporates the full range of reciprocal space information. Such detectors enable a versatile 4D‐STEM imaging mode, which is comprised of full diffraction (i.e., CBED) patterns, containing important information on the crystal structure,272 chemical composition,273 electric fields,274 defects/disorder,275 and strains,276–278 etc., for each probe position ( Figure ) 267,279,280…”
Section: Technological and Methodological Innovationsmentioning
confidence: 99%
“…As a special type of segmented detectors, pixelated detectors provide an ultimate detector form for STEM imaging that incorporates the full range of reciprocal space information. Such detectors enable a versatile 4D‐STEM imaging mode, which is comprised of full diffraction (i.e., CBED) patterns, containing important information on the crystal structure,272 chemical composition,273 electric fields,274 defects/disorder,275 and strains,276–278 etc., for each probe position ( Figure ) 267,279,280…”
Section: Technological and Methodological Innovationsmentioning
confidence: 99%
“…SCEM depth-sectioning measurements can also be performed using 4D-STEM. Hamaoka et al (2018) demonstrated that by using an annular aperture below the specimen and recording the full diffraction pattern, 3D information from the sample could be obtained using virtual ring detectors.…”
Section: Real-space 4d-stemmentioning
confidence: 99%
“…One of the potentials of SCEM is to reveal the 3D information on the sample without the need for sample tilting, as SCEM improves the depth resolution. The depth-sectioning measurements can be performed by placing a pinhole aperture at a conjugate plane that can block electrons outside the focal plane, akin to the working mechanism of confocal optical microscopy . Comparing to electron tomography, SCEM also faces challenges such as achieving a high spatial resolution, penetration depth, and a large field of view.…”
Section: Local Structural Order and Defects Characterized By Electron...mentioning
confidence: 99%
“…The depth-sectioning measurements can be performed by placing a pinhole aperture at a conjugate plane that can block electrons outside the focal plane, akin to the working mechanism of confocal optical microscopy. 279 Comparing to electron tomography, SCEM also faces challenges such as achieving a high spatial resolution, penetration depth, and a large field of view. Note that all these electron diffraction techniques can further be integrated with the atomic pair distribution function (PDF) analysis to quantify structurally disordered materials in terms of short-and medium-range ordering.…”
Section: Introduction To Electron Diffraction Techniquesmentioning
confidence: 99%